Exploring the spatial spillover effects of low-grade coal consumption and influencing factors in China. (March 2021) - Wang, Shaobin; Zhao, Chao; Liu, Hanbin; Tian, Xinglei
Abstract: The residential consumption of low-grade coal (LGC) is a serious threat to the environment and human health in China. In this study, spatial patterns and spatial spillover effects of LGC consumption in China were investigated. The LGC consumption data, economic, household expenditure, income, and energy consumption data at the provincial-level in mainland China were collected. Global/local spatial autocorrelation and spatial regression models were employed. The results presented a significant positive spatial autocorrelation and an obvious spatial clustering feature of LGC consumption in China. Furthermore, the spatial spillover effect of LGC consumption wan detected based on spatial lag modeling. Our result further revealed that LGC consumption is significantly related to energy consumption factors rather than economic and income factors, which is contrary to conventional assumptions about the energy transition but fits well with the fuel stacking model. Additionally, this study provides several implications for residential energy improvement in China, which calls for further policies, e.g., building a specific and strict management system to prohibit of LGC for residential consumption and improving the energy consumption structure, especially in the provinces with a high value of LGC consumption in the middle, southwestern, and northeastern parts of China. Highlights: Spatial autocorrelation and clustering features of LGC consumption in China were identified. The spatial spillover effect of LGC consumption was detected. Coal/energy consumption considered as the main influencing factors of LGC consumption. Economic indicators were not identified significantly influence of LGC consumption. Further implications for energy improvement policies of LGC in China were proposed.